Standardization of instantaneous fluoroprobe measurements of benthic algal biomass and composition in streams. (February 2021) - Rosero-López, D.; Walter, M.T.; Flecker, A.S.; Ontaneda, D.F.; Dangles, O.
Highlights: Regular chlorophyll-a monitoring helps promptly detect benthic algal proliferation. Chlorophyll-a in benthic algal substrates varies with the mat formation stages. Specific artificial substrates can be used for monitoring benthic algae in streams. Fluoroprobes enable benthic alga replicate collection and increase sampling area. Abstract: Fluoroprobes, such as BenthoTorch, offer a relatively rapid in situ method for monitoring benthic algae, provide new opportunities for aquatic ecological research, and enable early warning of algal proliferation in municipal water supplies. Currently, however, BenthoTorch is limited for the measurement of heterogeneous samples, and homogenizing samples is rather difficult. In this study, we compared chlorophyll-a (Chl-a) measurements between BenthoTorch and standard laboratory methods to quantify and describe the biomass and biovolume proportion of benthic algae growing on artificial and natural substrates. We used the difference in Chl-a measurements between these methods (n = 359) to evaluate the effects of environmental variables. Moreover, we used artificial and natural substrates to determine whether either of them reduced variation in BenthoTorch measurements. There was a general concordance in measurements between the two methods, but this agreement was stronger for artificial substrates. Artificial substrates also led to significantly less variation in BenthoTorch readings compared with natural substrates. This may be attributed to the formation of relatively thin algal mats on artificial substrates. To enable early warning of algal proliferation in an aquatic ecosystem, we recommend the use of BenthoTorch and artificial substrates combined with appropriate calibration using standard laboratory methods. The ability of BenthoTorch to produce instantaneous results facilitates replicate collection, which reduces sampling error and increases sampling area on the same day. Despite substantial variation in readings on natural substrates, BenthoTorch enables relatively rapid measurements, facilitating easy monitoring of large areas. Therefore, BenthoTorch may be worth incorporating into aquatic ecosystem studies, depending on the specific research questions.